Analisis Pelaksanaan Perkawinan Adat Banjar Kalimantan Selatan di DKI Jakarta - Febyola Febyola; Jenny Sista Siregar; Lilis Jubaedah (Departement of Mathematics Education, 2024)
The Banjar tribe has a tradition of being called